Effects of cysteine on goat sperm quality in cryopreservation - Khuong, Tran Thi Thanh; Duy, Nguyen Lam Khanh; Nhi, Le Thi Yen (Vietnam Journal of Biotechnology, 2024)
Cryopreservation is an effective method for long-term storage of sperm. It is essential to investigate the optimal conditions for preserving semen for the purpose of artificial insemination. Cysteine has been proven to reduce the extent of sperm damage caused by oxidative stress during cryopreservation. The aim of this study was to determine the concentration of cysteine required for cryopreservation of goat semen. The experiment was carried out on 2 bucks with 4 treatments, each treatment repeated 8 times. Goat semen was diluted with cryopreservation medium supplemented with cysteine at 4 concentrations: 0 mM, 2 mM, 5 mM, and 10 mM. The sample was transferred to a straw at 0.5 mL, then stored in a liquid nitrogen container. The samples were then thawed, and the sperm quality was evaluated after 72 hours of storage. The results showed that the treatment with 5 mM cysteine showed the best sperm quality results, and the difference was statistically significant with the rest of the treatments (P < 0.05). Specifically, the overall motility, viability, and membrane integrity of spermatozoa in the most optimal treatment were: 82.21%, 90.71%, and 76.09%, respectively. In summary, the study showed that adding a 5 mM concentration of cysteine to the cryopreservation medium significantly enhanced sperm quality